Association between rs1815739 polymorphism of ACTN3 gene and athletic ability in Chinese sprinters - Chen, W.; Zhang, B.; Li, Y.; Liang, T. (Journal of Science in Sport and Exercise, 2020)
Purpose: The aim of this study was to investigate the prevalence of the ACTN3 rs1815739 polymorphism and to study its association with athletes` level of competition and lower-extremity power. Method: Time-of-flight mass spectrometry (TOFMS) and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) techniques were employed to identify the ACTN3 rs1815739 genotypes and allele frequencies in 108 elite sprinters and 206 untrained controls. Questionnaires were then used to assess subjects` 100 m sprint, standing jump (SJ) and standing triple jump (STJ) personal best record. Results: (1) The RR, RX and XX genotype distribution of the ACTN3 rs1815739 polymorphism is 42.6%, 49.1%, 8.3%, respectively. R and X alleles frequency is 67.1% and 32.9%, respectively, which comply with Hardy Weinberg equilibrium (HWE) through Chi-square tests (Chi2 = 0.661; df = 2; P = 0.718). (2) Significant differences were found in R allele frequency between the elite sprinter group and controls. (3) The athletes` 100 m sprint, SJ, and STJ personal best records were better in those with RR and RX than XX genotype. A significant association was observed between the R alleles and 100 m sprint, SJ, and STJ results of male and female athletes. Conclusion: The present results indicate that ACTN3 rs1815739 polymorphism has a significant association with speed and lower-extremity power in sprint/power athletes.